Time to death and its associated factors among infants in sub-Saharan Africa using the recent demographic and health surveys: shared frailty survival analysis - Sofonyas Abebaw Tiruneh; Ejigu Gebeye Zeleke; Yaregal Animut (BMC, 2021)
Abstract Background Globally, approximately 4.1 million infants died, accounting for 75% of all under-five deaths. In sub-Saharan Africa (SSA), infant mortality was 52.7/1000 live births in 2018 This study aimed to assess the pooled estimate of infant mortality rate (IMR), time to death, and its associated factors in SSA using the recent demographic and health survey dataset between 2010 and 2018. Methods Data were retrieved from the standard demographic and health survey datasets among 33 SSA countries. A total of 93,765 samples were included. The data were cleaned using Microsoft Excel and STATA software. Data analysis was done using R and STATA software. Parametric shared frailty survival analysis was employed. Statistical significance was declared as a two-side P-value < 0.05. Results The pooled estimate of IMR in SSA was 51 per 1000 live births (95% Confidence Interval (CI): 46.65-55.21). The pooled estimate of the IMR was 53 in Central, 44 in Eastern, 44 in Southern, and 57 in Western Africa per 1000 live births. The cumulative survival probability at the end of 1 year was 56%. Multiple births (Adjusted Hazard ratio (AHR) = 2.68, 95% CI: 2.54-2.82), low birth weight infants (AHR = 1.28, 95% CI: 1.22-1.34), teenage pregnancy (AHR = 1.19, 95 CI: 1.10-1.29), preceding birth interval <  18 months (AHR = 3.27, 95% CI: 3.10-3.45), birth order ≥ four (AHR = 1.14, 95% CI:1.10-1.19), home delivery (AHR = 1.08, 95% CI: 1.04-1.13), and unimproved water source (AHR = 1.07, 95% CI: 1.01-1.13), female sex (AHR = 0.86, 95% CI: 0.83-0.89), immediately breastfeed (AHR = 0.24, 95% CI: 0.23-0.25), and educated mother (AHR = 0.88, 95% CI: 0.82-0. 95) and educated father (AHR = 0.90, 95% CI: 0.85-0.96) were statistically significant factors for infant mortality. Conclusion Significant number of infants died in SSA. The most common cause of infant death is a preventable bio-demographic factor. To reduce infant mortality in the region, policymakers and other stakeholders should pay attention to preventable bio-demographic risk factors, enhance women education and improved water sources.